Pengaruh Stres Kerja dan Motivasi Kerja terhadap Kinerja Pegawai pada PT. PLN Unit Pelaksana Pelayanan Pelanggan (UP3) Bandengan - Panji Areta; Aswin Naldi Sahim; Irawan R. D Budianto (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This study addresses the issue of employee performance which is influenced by work stress and work motivation at PT. PLN Customer Service Implementation Unit (UP3) Bandengan. The purpose of this research is to examine the partial and simultaneous effects of work stress and work motivation on employee performance, as well as to identify the most dominant influencing variable. This research employs a quantitative approach with an associative descriptive design. The population consisted of 66 employees, and all were used as respondents through a saturated sampling technique. Data were analyzed using statistical methods with SPSS software. The results indicate that work stress has a positive relationship with employee performance; however, statistically it does not have a significant effect. Meanwhile, work motivation has a positive and significant effect on employee performance. Simultaneously, work stress and work motivation significantly influence employee performance, with work motivation identified as the most dominant variable. These findings highlight the importance of strengthening employee motivation to achieve optimal performance while managing work stress effectively.